2014
DOI: 10.1007/s12031-013-0215-1
|View full text |Cite
|
Sign up to set email alerts
|

Bex2 Controls Proliferation of Human Glioblastoma Cells Through NF-κB Signaling Pathway

Abstract: Glioblastoma is the most common and fatal human brain malignancy in adults with highly proliferative capacity. Despite advances in surgery and adjuvant therapy, the median survival of patients has changed little over recent decades. Identifying molecules critical for glioma development is significant for devising effective targeted therapy. We previously reported that Bex2, a member of the brain expressed X-linked gene family, promoted the progression of glioma by promoting cell proliferation. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…P53 is a well-known pro-apoptotic molecule, and others have seen increases in apoptotic markers 17 and decreases in proliferation in GBM upon downregulation of NF-ĸB. 18,19 GBM stem cells from patient samples which express FACT show an increase in apoptosis upon treatment with CBL0137. 20 These results further suggest that glioma is responsive to CBL0137 and that CBL0137 would be a beneficial treatment.…”
Section: Discussionmentioning
confidence: 97%
“…P53 is a well-known pro-apoptotic molecule, and others have seen increases in apoptotic markers 17 and decreases in proliferation in GBM upon downregulation of NF-ĸB. 18,19 GBM stem cells from patient samples which express FACT show an increase in apoptosis upon treatment with CBL0137. 20 These results further suggest that glioma is responsive to CBL0137 and that CBL0137 would be a beneficial treatment.…”
Section: Discussionmentioning
confidence: 97%
“…However, BEX2 is highly expressed in a subset of estrogen receptor-positive breast cancers 10 and glioblastoma 11 and plays a key role in promoting cell survival and growth in breast cancer cells. The BEX protein family has been reported to contain long regions of intrinsic disorder that may form signaling hubs, and the hubs formed by intrinsically disordered proteins play important roles in cellular differentiation and cancer 6.…”
Section: Discussionmentioning
confidence: 99%
“…BEX2 is highly expressed in the embryonic brain and can interact with transcriptional factor LMO2 to regulate transcriptional activity 8. In addition, BEX2 has been reported to be involved in tumor development in several types of cancer, such as glioblastoma, glioma and breast cancer 9-11. Naderi et al found that BEX2 was up-regulated in a subset of primary breast cancers and that down-regulation of BEX2 induced G1-phase arrest in breast cancer cell lines 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another report examining 32 gliomas vs 15 nontumor tissues showed that BEX2 expression was 2.73 fold upregulated in glioma [26]. Selective depletion of BEX2 expression in glioma cells led to reduction of U251 cell proliferation, while 8 overexpression resulted in elevated cell proliferation [26,80]. Similar to the breast cancer cells, BEX2 expression enhanced p65 expression as well as activation of NF-κB pathway in the U251 cells.…”
Section: Bex Proteins In Gliomasmentioning
confidence: 98%